2022
DOI: 10.3390/ijerph19094955
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Efficacy, Work-Related Autonomy and Work-Family Conflict on Employee’s Stress Level during Home-Based Remote Work in Germany

Abstract: Home-based remote work becomes increasingly popular. The facets of remote work, especially working from home, are multifaceted and can become stressors that affect a person’s health. At the same time, self-efficacy is an important personal resource to deal with health-related stressors. The objective of this study is therefore to explore the relationship between self-efficacy (SE), work-related stress (WRS), health outcomes (health and anxiety), contributing factors (autonomy and experience) and work-family co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 105 publications
(164 reference statements)
5
39
1
Order By: Relevance
“…Contrary to expectations, this study finds that autonomy does not significantly affect work stress. It does not support previous studies, such as the Lange and Kayser (2022) and Schiff and Leip (2019) studies, which found that autonomy negatively affected work stress. These results indicate that some respondents perceive the existence of autonomy as reducing their stress, but for some it will increase their stress.…”
Section: Table 3 the Structural Model Test Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to expectations, this study finds that autonomy does not significantly affect work stress. It does not support previous studies, such as the Lange and Kayser (2022) and Schiff and Leip (2019) studies, which found that autonomy negatively affected work stress. These results indicate that some respondents perceive the existence of autonomy as reducing their stress, but for some it will increase their stress.…”
Section: Table 3 the Structural Model Test Resultscontrasting
confidence: 99%
“…However, with autonomy, people can manage their schedules and work on their tasks to reduce stress (Emre & De Spiegeleare, 2021). Empirically, autonomy was negatively related to work stress (e.g., Lange & Kayser, 2022;Schiff & Leip, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It was found in previous studies that a significant cause of the increased perceived work-related stress by workers is the interference between work and private life. The authors identified that for men, high demands of work, insecurity, stress at work and home were the main aspects correlated with more symptoms of depression and anxiety (25,26) . This same correlation with symptoms was identified for job insecurity and stress at home for women.…”
Section: Discussionmentioning
confidence: 99%
“…[14] "Work-family conflict is associated with a strong gender dependency, as in most cultures women are predominantly responsible for housework and caregiving." [15] Based on the results of research, conducted by Novitasari et al, it can be "concluded that work-family conflict gives negative and ISSN 2449-2418 P.…”
Section: Conflict Managementmentioning
confidence: 99%
“…Special attention should be paid to the emotional state and role conflicts of remote employees. "Previous studies suggest that an independent leadership style amplifies the influence on self-efficacy positively" [15]which can be used in the formation of conflict management style of remote employees.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%